ESTIMASI POPULASI ORANGUTAN (Pongo pygmaeus Wurmbii) DI TAMAN HUTAN RAYA LAPAK JARU KABUPATEN GUNUNG MAS PROVINSI KALIMANTAN TENGAH - Fauzi, Fouad; Aisyah, Siti; Oktavianus, Rob; Rizal, Moh.; Herianto, Herianto; Pidjat, Chartina; Hidayat, N. (Lambung Mangkurat University-Indonesia, 2024)
This research aims to determine the nest density and population of orangutans and the characteristics of orangutan nests in the Lapak Jaru Grand Forest Park (Tahura), Gunung Mas Regency, Central Kalimantan Province. The method used is strip transect, namely by making a path 1000 m long and 20 m wide on each side of the path and a total of 10 lanes. The calculation results of the average density of orangutan nests at the research location were 30.99 nests/km2 and the Orangutan population is estimated at 29.36 Orangutan individuals. The type of tree where most nests are found is Merawan (Silver sp), Meranti (Shorea sp), and Bumps/Bleeding (Santiria corferta) and based on the most dominant family is the Dipterocarpaceae family. The height of the tree where orangutans nest is 11-15 m with a percentage of 21.67%. The most commonly found diameter of nesting trees is 11-20 cm in diameter with a percentage of 64.67%. The nest height most preferred by orangutans is 16-20 m with a percentage of 28.30%. The most frequently found orangutan nest class is class 3 with a percentage of 35.85% and class 4 with a percentage of 33.96%, and the most frequently found orangutan nest position in the research location is position 2 with a percentage of 37.74%.